Un estudio económico de la mortalidad infantil en el Ecuador periodo 1989-2020 - Abad Jimenez, Paola del Cisne (2024)
In 2020, the infant mortality rate in Ecuador reached a value of 7.7 per thousand live births, which indicates that it continues to be a serious problem in society, showing that children born in conditions of poverty are twice as likely to die due to various social and economic factors present in the country. In short, the general objective of this research is to evaluate the relationship between the situation of the infant mortality rate and socioeconomic factors in Ecuador in the period 1989-2020. The World Bank database was used to collect statistical data on the variables to be used. Likewise, the time series methodology and the VAR model were used to measure the long-term relationship. The results obtained have shown the evolution of the variables and their behavior with respect to infant mortality, which made it possible to measure the degree of influence between them over time, and a long-term relationship between the mortality rate and the socioeconomic factors in the study has been evidenced. In conclusion, it is recommended that the government should establish mechanisms to raise the level of education in rural areas, since the cases of infant mortality in these areas are higher due to the shortage of professionals, so it is important to increase the number of professionals to help guide future mothers in a better way, so that infants and mothers have better attention in the area of health and their living conditions can improve and therefore, lead a better standard of living.